Applications of DNA Technology to Wildlife Forensic Science - Wilson, Paul J. (My University, 1996)
Molecular genetic protocols have been developed to provide evidence in infractions of wildlife statutes in Canada. We have utilized DNA marker systems to address specific questions in wildlife investigations based on their different levels of genetic variability. Multilocus DNA fingerprinting has been applied to poaching infractions to determine if tissue samples associated with a suspected poacher originated from the remains of an animal at a known illegal kill site. The hypervariability of the variable number of tandem repeat (VNTR) loci detected by multilocus DNA fingerprinting allows the individual identification of samples. Highly repetitive satellite DNA markers have been applied to determining the species of origin of unknown tissue samples based on their species-specificity. Satellite DNA profiling have provided evidence in illegal commercialization investigations involving species such as moose (Alcesalces) and white-tailed deer (Odocoileus virginianus), including the illegal addition of game meat in processed meat products. A sex-specific DNA locus, the sex-determining region on the Y-chromosome (Sry), has been utilized to determine the sex of cervid samples that have had gender-specific physical characteristics, antlers and genitalia removed in violation of the validation tag system. Finally, a polymerase chain reaction (PCR) based protocol has been established for the species identification of samples that produce minute amounts of DNA or degraded DNA. Cytochrome b sequences demonstrate low intra-specific levels of sequence divergence and higher inter-specific levels of sequence divergence. Cytochrome b sequence analysis has been applied to fish, game and domestic species commonly involved in wildlife investigations and to the identification o fa number of species, mostly seal species, involved in the trade of animal parts.
Keywords: Wildlife Forensic Science; Molecular Genetic Protocols; Canada; Poaching; DNA fingerprinting